Evaluation of a hepatitis C clinical care coordination programme's effect on treatment initiation and cure: A surveillance‐based propensity score matching approach. Issue 11 (24th May 2018) - Deming, R.; Ford, M. M.; Moore, M. S.; Lim, S.; Perumalswami, P.; Weiss, J.; Wyatt, B.; Shukla, S.; Litwin, A.; Reynoso, S.; Laraque, F.
Abstract: Hepatitis C (HCV) is a viral infection that if left untreated can severely damage the liver. Project INSPIRE was a 3 year HCV care coordination programme in New York City (NYC) that aimed to address barriers to treatment initiation and cure by providing patients with supportive services and health promotion. We examined whether enrolment in Project INSPIRE was associated with differences in HCV treatment and cure compared with a demographically similar group not enrolled in the programme. INSPIRE participants in 2015 were matched with a cohort of HCV‐infected persons identified in the NYC surveillance registry, using full optimal matching on propensity scores and stratified by INSPIRE enrolment status. Conditional logistic regression was used to assess group differences in the two treatment outcomes. Two follow‐up sensitivity analyses using individual pair‐matched sets and the full unadjusted cohort were also conducted. Treatment was initiated by 72% (790/1130) of INSPIRE participants and 36% (11 960/32 819) of study‐eligible controls. Among initiators, 65% (514/790) of INSPIRE participants compared with 47% (5641/11 960) of controls achieved cure. In the matched analysis, enrolment in INSPIRE increased the odds of treatment initiation (OR: 5.25, 95% CI: 4.47‐6.17) and cure (OR: 2.52, 95% CI: 2.00‐3.16). Results from the sensitivity analyses showed agreement with the results from the full optimal match. Participation in the HCV care coordination programme significantly increased the probability of treatment initiation and cure, demonstrating that care coordination for HCV‐infected individuals improves treatment outcomes.